A descriptive study on selected growth parameters and growth hormone receptor gene in healthy young adults from the American Midwest. (August 2018) - Hartin, Samantha N.; Hossain, Waheeda A.; Manzardo, Ann M.; Brown, Shaquanna; Fite, Paula J.; Bortolato, Marco; Butler, Merlin G.
Abstract: Context: The first study of growth hormone receptor ( GHR ) genotypes in healthy young adults in the United States attending a Midwestern university and impact on selected growth parameters. Objective: To describe the frequency of GHR genotypes in a sample of healthy young adults from the United States attending a university in the Midwest and analyze the relationship between GHR genotypes and selected growth parameters. Design: Saliva was collected from 459 healthy young adults (237 females, 222 males; age range = 18–25 y) and DNA isolated for genotyping of GHR alleles ( fl/fl, fl/d3, or d3/d3 ). Selected growth parameters were collected and GHR genotype data examined for previously reported associations (e.g., height, weight or bone mass density) or novel findings (e.g., % body water and index finger length). Results: We found 219 participants (48%) homozygous for fl/fl, 203 (44%), heterozygous fl/d3 and 37 (8%) homozygous d3/d3. The distribution of GHR genotypes in our participants was consistent with previous reports of non-US populations. Several anthropometric measures differed by sex. The distribution of GHR genotypes did not significantly differ by sex, weight, or other anthropometric measures. However, the fl/d3 genotype was more common among African-Americans. Conclusions: Our study of growth and anthropometric parameters in relationship to GHR genotypes found no association with height, weight, right index finger length, BMI, bone mass density, % body fat or % body water in healthy young adults. We did identify sex differences with increased body fat, decreased bone density, body water and index finger length in females. Highlights: Description of GHR genotypes in healthy young adults living in the Midwest Collection of growth parameters and body composition measures No association between GHR genotypes and selected growth measures